Assessing the Early Response of Advanced Cervical Cancer to Neoadjuvant Chemotherapy Using Intravoxel Incoherent Motion Diffusion-weighted Magnetic Resonance Imaging: A Pilot Study - Wang, Yan-Chun (Chin Med J (Engl), 2016)
BACKGROUND: Diffusion-weighted imaging (DWI) with the intravoxel incoherent motion (IVIM) model has shown promising results for providing both diffusion and perfusion information in cervical cancer; however, its use to predict and monitor the efficacy of neoadjuvant chemotherapy (NACT) in cervical cancer is relatively rare. The study aimed to evaluate the use of DWI with IVIM and monoexponential models to predict and monitor the efficacy of NACT in cervical cancer. METHODS: Forty-two patients with primary cervical cancer underwent magnetic resonance exams at 3 time points (pre-NACT, 3 weeks after the first NACT cycle, and 3 weeks after the second NACT cycle). The response to treatment was determined according to the response evaluation criteria in solid tumors 3 weeks after the second NACT treatment, and the subjects were classified as two groups: responders and nonresponders groups. The apparent diffusion coefficient (ADC), true diffusion coefficient (D), perfusion-related pseudo-diffusion coefficient (D*), and perfusion fraction (f) values were determined. The differences in IVIM-derived variables and ADC between the different groups at the different time points were calculated using an independent samples t-test. RESULTS: The D and ADC values were all significantly higher for the responders than for the nonresponders at all 3 time points, but no significant differences were observed in the D* and f values. An analysis of the receiver operating characteristic (ROC) curves indicated that a D value threshold <0.93 × 10(−3) mm(2)/s and an ADC threshold <1.11 × 10(−3) mm(2)/s could differentiate responders from nonresponders at pre-NACT time point, yielding area under the curve (AUC) of which were 0.771 and 0.806, respectively. The ROC indicated that the AUCs of D and ADC at the 3 weeks after the first NACT cycle and 3 weeks after the second NACT cycle were 0.823, 0.763, and 0.787, 0.794, respectively. The AUC values of D and ADC at these 3 time points were not significantly different (P = 0.641, 0.512, and 0.547, respectively). CONCLUSIONS: D and ADC values may be useful for predicting and monitoring the efficacy of NACT in cervical cancer. An IVIM model may be equal to monoexponential model in predicting and monitoring the efficacy of NACT in cervical cancer.